2017
DOI: 10.17265/1539-8072/2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

DISE Learning Model for Teaching Writing to Elementary School Students

Abstract: DISE learning model refers to the one which is dialogue-based using scientific approach containing edutainment element. DISE is the acronym of dialog, scientific, and edutainment. It is a learning model which is developed for the fifth graders of elementary school particularly for teaching writing of personal recount. This article described DISE learning model from the theoretical basis, meaning, and syntax. DISE was the product of Research and Development design conducted in Banyumas Regency, Central Java Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…(p. 5). Widosari et at. (2017) stated that writing is more demanding than the other language skills; a study done at Thaksin University to 28 third year English-minor students showed that learners faced writing problems which impacts the quality of written production (Bennui, 2016), and Ecuador is not an exception.…”
Section: Introductionmentioning
confidence: 99%
“…(p. 5). Widosari et at. (2017) stated that writing is more demanding than the other language skills; a study done at Thaksin University to 28 third year English-minor students showed that learners faced writing problems which impacts the quality of written production (Bennui, 2016), and Ecuador is not an exception.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this understanding, it could be defined that teaching strategies are the design of teachers in teaching; containing methods and techniques, which are used in the learning process. Suitable teaching strategies should be conducted because many people consider the writing subject as a challenging level of language skills (Widosari, Suwandi, Slamet, & Winarni, 2017). Teachers' strategies have occupied a significant role in teaching writing for young learners, for instance knowing the characteristics of the students.…”
Section: Introductionmentioning
confidence: 99%
“…In research done by David, Thang, and Azman (2015) in a higher education institution, learners reported that the most demanding skill was writing. Widosari, Suwandi, Slamet, and Winarni (2017) mentioned that learning writing is not as simple as studying the three other language skills. According to Graham, Harris, and McKeown (2013), the process of writing involves the use of different components such as grammar rules, structure, organization, and understanding of its purpose.…”
Section: Introductionmentioning
confidence: 99%